Endothelial Cell Insulin Signaling Regulates CXCR4 (C-X-C Motif Chemokine Receptor 4) and Limits Leukocyte Adhesion to Endothelium. Issue 7 (2nd June 2022) - Rathjen, Thomas; Kunkemoeller, Britta; Cederquist, Carly T.; Wang, Xuanchun; Lockhart, Sam M.; Patti, James C.; Willenbrock, Hanni; Olsen, Grith Skytte; Povlsen, Gro Klitgaard; Beck, Hans Christian; Rasmussen, Lars Melholt; Li, Qian; et al.
Abstract : Background: An activated, proinflammatory endothelium is a key feature in the development of complications of obesity and type 2 diabetes and can be caused by insulin resistance in endothelial cells. Methods: We analyzed primary human endothelial cells by RNA sequencing to discover novel insulin-regulated genes and used endothelial cell culture and animal models to characterize signaling through CXCR4 (C-X-C motif chemokine receptor 4) in endothelial cells. Results: CXCR4 was one of the genes most potently regulated by insulin, and this was mediated by PI3K (phosphatidylinositol 3-kinase), likely through FoxO1, which bound to the CXCR4 promoter. CXCR4 mRNA in CD31+ cells was 77% higher in mice with diet-induced obesity compared with lean controls and 37% higher in db/db mice than db/+ controls, consistent with upregulation of CXCR4 in endothelial cell insulin resistance. SDF-1 (stromal cell–derived factor-1)—the ligand for CXCR4—increased leukocyte adhesion to cultured endothelial cells. This effect was lost after deletion of CXCR4 by gene editing while 80% of the increase was prevented by treatment of endothelial cells with insulin. In vivo microscopy of mesenteric venules showed an increase in leukocyte rolling after intravenous injection of SDF-1, but most of this response was prevented in transgenic mice with endothelial overexpression of IRS-1 (insulin receptor substrate-1). Conclusions: Endothelial cell insulin signaling limits leukocyte/endothelial cell interaction induced by SDF-1 through downregulation of CXCR4. Improving insulin signaling in endothelial cells or inhibiting endothelial CXCR4 may reduce immune cell recruitment to the vascular wall or tissue parenchyma in insulin resistance and thereby help prevent several vascular complications.